FINANCIAL RESILIENCE: LEVEL OF SHARIA FINANCE LITERACY AND INCLUSION TOWARDS EXPANDING FINANCIAL ACCESS - Koko Bustami; Muhammad Saifrizal; Lakharis Inuzula (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
The urgency of the problem, several main indicators that support this achievement, include increasing financial access, accelerating the use of formal financial services, and improving the quality of financial services. The level of financial literacy in Indonesia is still lower than financial inclusion. Financial literacy has only reached 38.03%. while sharia financial literacy is 20.1%. To increase the level of financial literacy, education and outreach are carried out quite intensively by the National Council for Inclusive Finance. Apart from the general public, education and outreach is also carried out among students and micro and small businesses around Islamic boarding schools (ponpes) as priority groups, in accordance with the mandate of Presidential Regulation Number 114 of 2020 concerning the National Strategy for Inclusive Finance. Indonesia itself has more than 30 thousand Islamic boarding schools and more than 4.2 million Islamic boarding school students. Some of these Islamic boarding schools have great potential in the fields of agriculture, animal husbandry, fisheries and MSEs which can become a driving force for the people's economy, sharia economy and halal MSEs. The sharia financial literacy index in 2019 showed an increase, namely to 8.93% from the previous 8.1% in the previous survey period in 2016. The aim of this research is to determine whether or not there is a relationship between literacy and financial inclusion, whether literacy has a relationship with expanding access. finance, whether financial inclusion has a relationship to expanding financial access. and to measure the level of understanding of female students regarding financial literacy in increasing sharia financial inclusion towards expanding financial access. The ultimate goal of financial literacy and inclusion is the financial welfare of society or often referred to as financial well-being. One of the characteristics of financial well-being is financial resilience. Financial resilience is a condition where a person has the ability to overcome various problems and financial shocks that he or she may face. The output of this research is the publication of accredited National Scientific Articles, namely the Sean Institute Economic Journal with the achievement indicator "Letter of Accepted". The final level of Technology Readiness (TKT) for this research is at level 2 and will end at TKT 5.